GEOTECHNICAL DESIGN OF INDUSTRIAL BASED AUTOMOTIVE VOCATIONAL SCHOOL AT BEKASI REGENCY - Adie, Brahmantyo
Industrial Based Automotive Vocational School at Bekasi Regency consist of 3 building: student practice building, classroom building, and teacher office building. This final project scope is limited to the design process of student practice building. The objectives of this final project are: to analyze the potent geological problem at the project site, to analyze the needs based on the problem, and to design the geotechnical structure based on valid regulations. Based on the analysis result, is known that there is a settlement problem potential caused by a layer of soft consistency clay at 12 m of top elevation. This analysis result becomes the basis for determining the usage of deep foundations. The deep foundation type that is used is a circular spun pile with an 800 mm diameter and 13 m depth of penetration. In the foundation design, the axial and lateral bearing capacity was checked with help of LPILE and GROUP applications. Based on modeling results, 6 types of pile group configurations were used which were then checked for settlement against the existing settlement requirement. Afterward, reinforcement of the pile cap was designed and pile head treatment along with the design of tie beams with a size of 500 mm x 500 mm as a binder between foundations.